Cost-Effectiveness Analysis of Antibiotic Use in Patients with Chronic Obstructive Pulmonary Desease (COPD) - Pameswari, Puspa; Aria, Mimi; Zuhriah, Aminah (PT. Riset Press International, 2025)
Chronic obstructive pulmonary disease (COPD) is a disease with airway limitations that are not completely reversible due to harmful substances or gases. The most common cause of acute exacerbations of COPD is bacterial infection, so treatment that can be done is to use antibiotics. Ineffective drug therapy will affect the effectiveness and costs incurred by patients. The purpose of this study is to find out how cost-effective and antibiotic treatment are in patients with acute exacerbations of COPD. This study uses an observational descriptive method with retrospective data collection based on medical record data and the cost of using antibiotics for Chronic Obstructive Pulmonary Disease (COPD) acute exacerbations of hospitalization at hospitals. Dr. M. Djamil Padang in 2019-2021. The calculation result with the lowest CER was the combination of levofloxacin and ceftriaxone of Rp. 323.6 and an outcome value of 100%. It can be concluded that the most effective use of antibiotic therapy models in COPD patients with acute exacerbations is the combination of levofloxacin and ceftriaxone.